The relationships between eating disorder pathology and relative reinforcing value of food, delay discounting, and related constructs in adolescents. (1st May 2020) - Balantekin, Katherine N.; Ziegler, Amanda M.; Crandall, Amanda K.; Temple, Jennifer L.
Abstract: Food is a primary reinforcer that motivates behavior in the absence of learning or conditioning. Both the relative reinforcing value (RRV) of food and delay discounting are associated with weight status. While dietary restraint and disinhibition have been shown to influence the RRV of food, limited work has examined the relationships between eating disorder pathology and RRV of food and delay discounting. Therefore, the purpose of this study was to examine how eating disorder pathology predicts RRV of food, proportion of food consumed, delay discounting, reinforcement pathology (i.e., high motivation to eat and high delay discounting), and sensitization of high energy dense food (HED; i.e., increases in RRV of HED food after daily repeated exposure). Participants were 167 adolescents ages 12–14 without obesity participating in a longitudinal study examining predictors of weight change who completed a series of laboratory assessments assessing the RRV of food of HED food, delay discounting, reinforcement pathology, sensitization of HED food, and a questionnaire assessing eating disorder pathology. Eating disorder pathology was not related to the RRV of food or delay discounting, but did predict reinforcement pathology and the sensitization of HED food. When explored by weight status, these relationships were only observed for those with overweight. There were no other significant relationships for either adolescents with normal weight or overweight. Given that weight status appeared to moderate some of the relationships between eating disorder pathology and reinforcement-related constructs, future work should examine how reinforcement pathology and eating disorder pathology are related to changes in weight status over time.